The impact of the digital economy on green total factor productivity in Belt and Road countries: the mediating role of energy transition - Wang, Anqi; Ren, Junyu (Frontiers in Environmental Science, 2023)
The prospective Belt and Road (B&R) Initiative by China needs to be thoroughly examined in all respects by the participating nations. It is now important to investigate whether the digital economy of the B&R countries can support green total factor productivity (GTFP). This study examines the connection between the green total factor productivity (GTFP) and the digital economy in B&R countries with the aim of providing China practical recommendations for advancing the initiative. This research explores 40 B&R countries from 2006 to 2021, calculates the GTFP using the unexpected super-efficient SBM model and the Global Malmquist-Luenberger index method, constructs the digital economy Index using the principal component analysis method. For the digital economy-GTFP nexus, OLS, FMOLS methods and spatial panel regression are used. In the selected 40 Belt and Road countries, there is a nonlinear relationship between digital economy and GTFP, and the overall effect of digital economy on GTFP is negative, which implies the growth of the digital economy will cause a decline in GTFP. Energy transition has mediation effects that can weaken the negative impact of digital economic growth on GTFP. The spatial spillover effect of the digital economy on the GTFP of neighboring countries is evident, and there is spatial heterogeneity. The digital economy will reduce GTFP in high-income and middle-income countries, but the negative effects is not evidently in low-income countries. This paper adds to the discussion of the digital economy and green development by drawing different conclusions from previous studies using a variety of regression models, providing a new foundation for policy-making.